Gambaran Pola Asuh Orang Tua Yang Mengalami Kehamilan Pranikah Pada Usia Remaja Akhir - Zahra Danarasa, Khairya (CV RIFAINSTITUT, 2023)
This study aims to describe the parenting style of parents who experience premarital pregnancies. This study involved four individuals who had experienced premarital pregnancies in their late adolescents. The first subject was 24 years old, the second subject was 26 years old, the third subject was 22 years old, and the fourth subject was 20 years old. The research method used is qualitative with an intrinsic case study approach. The data mining technique uses general guideline interviews and the analysis used is thematic analysis with theory driven so that the researchers can use existing theories in data coding. The results of this study indicate that of the four subjects, they do not tend to have one parenting style. However, the parenting style is adopted to the situation and conditions that the subject is facing. In addition, late adolescents who experience premarital pregnancies tend to be less prepared financially and psychologically.